Fiscal Decentralization Generates Economic Growth: Evidence from Province-Level Cross-Section Data for Indonesia - Jhon Talbu Ritonga; Muhammad Zilal Hamzah (Universitas Trisakti, 2006)
Recently, fiscal decentralization, which involves the devolution of government fiscal responsibilities to lower levels of government, has been discussed in many developed and developing countries. In particular, the effect of fiscal decentralization on economic growth is a key issue in recent theoretical and empirical studies in public finance. The empirical evidences produce mixed results. In this study, the effect of fiscal decentralization on economic growth in a sample of several provinces will be explored. A province study offers several advantages: a bigger sample of data is available for province than for Indonesia; and panel data estimation is able to adjust the cultural, historical, and institutional differences and also to capture the local heterogeneities. By adopting a production-function-based estimation framework, the empirical estimation is done on a sample of cross section data that comprises of 26 province governments and the time series yearly data from 1992 to 2002. The Generalized Least Square method is used to test these data. The results indicate that: first, the fiscal decentralization variables (expenditure indicator) show the positive and significant coefficients, while, the revenue indicator shows the negative relationship with economic growth. Hence, several policy implications can be derived; i.e, the local government should be able: to increase their non taxes revenues; to create conducive conditions for capital inflows; and to develop a clear framework for fiscal decentralization assignment such as income redistribution and borrowingJEL classification: E60; E62; H62; H63; 04Keywords: province government financing; fiscal decentralization;localautonomy;fiscal policy; economic growth; cross-province data;